Pulmonary hypertension classification based on machine learning using standart chest X-ray:ATA artificial intelligence study-1 - Tarik, T.; Yagmur, B.; Kocakaya, D.; Sinan, U. Y.; Sekerci, S. Sert; Yayla, C.; Zoghi, M. (Wiley, 2023)
[Abstract Not Available]